Effect of SMILE guide intervention on knowledge about bad habits of grade 5 students at SDN 10 Sungai Sapih Padang: Pengaruh intervensi panduan SMILE terhadap pengetahuan tentang kebiasaan buruk siswa kelas 5 SDN 10 Sungai Sapih Padang - Kevin Amri Gesta; Satria Yandi; Intan Batura Endo Mahata (Makassar Dental Journal PDGI Makassar, 2023)
State Elementary School 10 Sungai Sapih is a school assisted by the Faculty of Dentistry, Baiturrahmah University as a re-search location to increase knowledge about children's bad habits so that children can maintain their oral health according to the zero caries 2030 programme. Senyum Masyarakat Indonesia Lebih Sehat (SMILE) Guidebook is information about oral health in pregnant women, children and adolescents. This article provides knowledge to people who do not know much about oral health, especially in pregnant women, children and adolescents. This study is a pre-experimental with one-group prestest-posttest design with a total of 56 samples taken by simple random sampling. Data were obtained by giving questionnaires to 5th grade children. The average knowledge before being given the book media intervention was the moderate category (41.7%) and after being given the book media intervention increased to mostly good category (76.7%). It is concluded that the use of SMILE guidebook media has an effect on knowledge about bad habits of grade 5 children at SDN 10 Sungai Sapih Padang.